Infusion System Carrier Flow Perturbations and Dead-Volume. (June 2015) - Lovich, Mark A.; Pezone, Matthew J.; Maslov, Mikhail Y.; Murray, Michael R.; Wakim, Matthew G.; Peterfreund, Robert A.
<x xml:space="preserve">Abstract</x> BACKGROUND: We have previously shown that, at constant carrier flow, drug infusion systems with large dead-volumes (V) slow the time to steady-state drug delivery in vitro and pharmacodynamic effect in vivo compared to those with smaller V. In this study, we tested whether clinically relevant alterations in carrier flow generate perturbations in drug delivery and pharmacodynamic effect, and how these might be magnified when V is large. METHODS: Drug delivery in vitro or mean arterial blood pressure (MAP) and ventricular contractility (max dP/dt) in a swine model were quantified during an infusion of norepinephrine (fixed rate 3 mL/h) with a crystalloid carrier (10 mL/h). The carrier flow was transiently halted for either 10 minutes or 20 minutes and then restarted. In separate experiments, a second drug infusion (50 mL over 10 minutes) was introduced into the same catheter lumen used by a steady-state norepinephrine infusion. The resulting perturbations in drug delivery and biologic effect were compared between drug infusion systems with large and small V. RESULTS: Halting carrier flow immediately decreased drug delivery in vitro, and MAP and max dP/dt. These returned to steady state before restarting carrier flow with the small, but not the large, V. Resuming carrier flow after 10 minutes resulted in a transient increase in drug delivery in vitro and max dP/dt in vivo, which were of longer duration and greater area under the curve (AUC) for larger V. MAP also increased for longer duration for larger V. Resuming the carrier flow after 20 minutes resulted in greater AUCs for drug delivery, MAP, and max dP/dt for the larger V. Adding a second infusion to a steady-state norepinephrine plus carrier flow initially resulted in a drug bolus in vitro and augmented contractility response in vivo, both greater with a larger V. Steady-state drug delivery resumed before the secondary infusion finished. After the end of the secondary infusion drug delivery, MAP and max dP/dt decreased over minutes. Drug delivery and max dP/dt returned to steady state more quickly with the small V. CONCLUSIONS: Stopping and resuming a carrier flow, or introducing a second medication infusion, impacts drug delivery in vitro and biologic response in vivo. Infusion systems with small dead-volumes minimize these perturbations and dampen the resulting hemodynamic instability. Alterations in carrier flow impact drug delivery, resulting in substantial effects on physiologic responses. Therefore, infusion systems for vasoactive drugs should be configured with small V when possible.